Laboratory‐modified powder diffraction specimen holder for filter paper. Issue 6 (25th October 2020) - Rowles, Matthew R.
Abstract : A simple way to modify powder diffraction specimen holders to allow for the presentation of filter papers is given. Abstract : A simple modification to an existing powder diffraction specimen holder is given to allow for the presentation of filter papers for analysis. A mild steel annulus holds the filter paper in place using magnets added to the rear of the specimen holder.